2015
DOI: 10.1016/j.jenvman.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fresh and mature organic amendments on the phytoremediation of technosols contaminated with high concentrations of trace elements

Abstract: Organic compounds resulting from the decomposition of organic amendments are used in the remediation of trace element (TE) contaminated soils. The mobility, phytoavailability and soil exposure intensity of molybdenum (Mo), chromium (Cr), zinc (Zn), copper (Cu), Cobalt (Co) and Arsenic (As) were evaluated in the phytoremediation of contaminated technosols after the addition of two organic matter types, fresh ramial chipped wood (RCW) and composted sewage sludge (CSS). The experiment consisted of nine main treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 55 publications
(54 reference statements)
1
16
1
1
Order By: Relevance
“…2.a). Total dissolved Cu concentrations in the SPW increased in 2010 and 2011 linearly with total soil Cu (R² > 0.9) confirming previous findings (Hattab et al, 2015). This agreed with Gonzalez et al (2014), Kolbas et al (2011) and Salati et al (2010) who tested the efficiency of phytoextraction to reduce Cu excess in the soil pore water.…”
Section: Mobility Of Cu Cr Zn and Assupporting
confidence: 90%
“…2.a). Total dissolved Cu concentrations in the SPW increased in 2010 and 2011 linearly with total soil Cu (R² > 0.9) confirming previous findings (Hattab et al, 2015). This agreed with Gonzalez et al (2014), Kolbas et al (2011) and Salati et al (2010) who tested the efficiency of phytoextraction to reduce Cu excess in the soil pore water.…”
Section: Mobility Of Cu Cr Zn and Assupporting
confidence: 90%
“…The use of compost improved Pb concentration in the plant tissue (Figure 1). Hattab et al (2015) studied the effect of fresh and mature organic material on phytoremediation technique. They concluded that the use of compost improved the plant growth and Zu and Cu concentrations in the peanut.…”
Section: Pb Concentration In Plantmentioning
confidence: 99%
“…In the restoration of contaminated soils, the use of organic amendments is widespread (Ciadamidaro et al, 2015;Hattab et al, 2015;Montiel-Rozas et al, 2015) but the effect of them on LMWOA exudate by roots has been scarcely studied. A few previous studies have reported the increase of LMWOAs release in soil solution due to the amendment addition (Peña et al, 2015).…”
Section: Introductionmentioning
confidence: 99%